Rancang Bangun dan Evaluasi Sistem Smart-Ponik Untuk Monitoring dan Automatisasi Tanaman Hidroponik Berbasis IOT dengan Protokol MQTT QTT - Siti Aulia Rachmini; Muh. Rafli Rasyid; Chairi Nur Insani; Alim Rabbani (Journal of Applied Computer Science and Technology, 2025)
Hydroponic farming, a soil-free farming method that has grown in popularity due to its efficient land use and ability to deliver high-quality yields. However, when managed manually, it often encounters issues such as inaccurate watering, imprecise nutrient regulation, and delays in detecting environmental changes. These factors can lead to reduced productivity and lower crop quality. This research aims to address these issues by developing Smart-Ponik, an Internet of Things (IoT)-based monitoring and automation system for hydroponic cultivation utilizing the Message Queuing Telemetry Transport (MQTT) protocol. The system integrates DHT22, soil moisture, and pH sensors to monitor key environmental parameters and transmits data in real time to a server for visualization through a web-based dashboard and automated notifications. The study employs a Research and Development (R&D) method consisting of needs analysis, system design, implementation, and testing. Experimental results show that the system achieves a 100% data transmission rate without packet loss, with an average latency of 0.00 seconds, and occasional delays of 0.01–0.02 seconds due to network fluctuations. Automated control of pumps and fans records a 95% success rate, while black-box testing demonstrates a 100% functional pass rate. In conclusion, Smart-Ponik proves effective for real-time monitoring and automation of hydroponic environments. The system minimizes manual errors, enhances environmental stability, and supports more consistent crop yields. These findings highlight the potential of IoT-based automation to improve precision agriculture practices and increase the reliability of hydroponic production.